Reinforcing the Role of Cyber Village in Improving Indonesia MSMEs Through an Exploratory Study - Anindita, Rina; Prastowo, Valentinus Hartadi; Parker, Jonathan (Aptisi Transactions On Technopreneurship (ATT), 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, especially those offering culturally unique products, face challenges in sustaining and growing their businesses. Digital marketing, particularly through social media, presents an opportunity to foster the development of these enterprises. However, the adoption of digital marketing by MSMEs in Kampoeng Cyber Jogja remains underexplored. This qualitative research aims to assess the extent of digital marketing adoption among MSMEs in Kampoeng Cyber Jogja and identify the factors that support or hinder its use. Data were collected through in-depth interviews with Kampoeng Cyber pioneers, MSME actors, the Head of RW09, and a digital marketing expert. The findings show that MSMEs in Kampoeng Cyber Jogja use social media for advertising, sharing product information, customer engagement, and selling products. Supporting factors include high-quality products and strong entrepreneurial motivation, while hindering factors include limited knowledge, slow adaptation to technology, resource constraints, and disorganized bookkeeping. This study suggests that MSMEs in Kampoeng Cyber Jogja need to set more explicit business goals to fully leverage digital marketing for scaling their businesses. Further research is needed to explore the long-term implications of digital marketing adoption and its impact on MSME sustainability and growth.